Optimization of raw acrylic yarn dye wastewater treatment by electrochemical processes: kinetic study and energy consumption - Ilhan, F.; Ulucan-Altuntas, K.; Dogan, C.; Kurt, U. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2019)
The textile industry has an important place in the environmental pollution due to its heavy water consumption and to the toxic content of dye. Every succeeding day, the water quality is deteriorated because the wastewater containing the dye is supplied to the receiving medium. In this study, The electrocoagulation and electrofenton processes, which produce less waste than the conventional methods and which are less costly, have been investigated for decolourization of acrylic yarn dyeing wastewater. The electrocoagulation process was involved four electrodes parallel connected. To optimize the treatment, response surface methodology (RSM) was applied. The operating independent conditions were selected as the current density (20-100 A/m(2)), reaction time (5-25 minutes) and initial pH (pH 4.3-pH 8.3). As a result of optimization by RSM method, the highest Colour, COD and TOC removal were obtained as 96.2%, 43.8% and 40.4 %, respectively. In order to obtain these results, it was necessary to apply a current density of 100 A/m(2) to the wastewater which has been set to an initial pH of 7.2 and 20.7 minutes. With the experimental setup installed, high colour removal can be achieved in as little as 15 minutes. Although the colour removal is high, COD removal does not meet discharge standards. Therefore, electrofenton process was applied for enhancing COD and TOC removal and removal rate increased to 70.0% and 61.5%, respectively. In order to study the removal mechanism for acrylic yarn dye wastewater by electrocoagulation process, kinetic modelling was applied. Energy consumption was also assessed.
Keywords: Electrofenton; electrocoagulation; parallel electrodes; aluminium; iron; kinetic modelling; energy consumption; AZO-DYE; DECOLORIZATION; WASTEWATERS; PARAMETERS; ALUMINUM; FE; Environmental Sciences & Ecology